PENGARUH KOMPETENSI SDM DAN PENERAPAN SIA TERHADAP KUALITAS LAPORAN KEUANGAN - Emkhad Arif; Zelnita Aulia Fitri (Journal Of Islamic Finance And Accounting Research, 2022)
The purpose of this study was to determine the effect of human resource competence and the application of accounting information systems on the quality of financial reports for small and medium enterprises. This research was conducted in Siak and Kandis Districts. The types of data used in this study are primary data and secondary data. Primary data is data obtained by quesioners with business employees or business owners who handle the preparation of financial statements. Secondary data is data obtained from documents and reports related to research. Data collection techniques used are interviews, questionnaires and documentation. While the data analysis technique is multiple linear regression analysis. The results showed that the variable of human resource competence had a significant effect on the quality of the financial statement of small and medium enterprises, while the application of an accounting information system had a significant effect on the quality of financial reports and the competence of human resources and the application of an accounting information system had a significant on the quality of business financial statement small and medium.